TAB2 deficiency induces dilated cardiomyopathy by promoting mitochondrial calcium overload in human iPSC-derived cardiomyocytes - Wenrui Sun; Jianchao Zhang; Shuang Li; Wanrong Fu; Yangyang Liu; Mengduan Liu; Jianzeng Dong; Xiaoyan Zhao; Xiaowei Li (Molecular Medicine)
Abstract Background TGF-β-activated kinase 1 binding protein 2 (TAB2) is an intermediary protein that links Tumor necrosis factor receptor 1 (TNFR1) and other receptor signals to the TGF-β-activated kinase 1 (TAK1) signaling complex. TAB2 frameshift mutations have been linked to dilated cardiomyopathy (DCM), while the exact mechanism needs further investigation. Methods In this study, we generated a TAB2 compound heterozygous knockout cell line in induced pluripotent stem cells (iPSCs) derived from a healthy individual using CRISPR/Cas9 technology. IPSCs are not species-dependent, are readily accessible, and raise fewer ethical concerns. Results TAB2 disruption had no impact on the cardiac differentiation of iPSCs and led to confirmed TAB2 deficiency in human iPSC-derived cardiomyocytes (hiPSC-CMs). TAB2-deficient hiPSC-CMs were found to develop phenotypic features of DCM, such as distorted sarcomeric ultrastructure, decreased contractility and energy production, and mitochondrial damage at day 30 post differentiation. Paradoxically, TAB2 knockout cell lines showed abnormal calcium handling after 40 days, later than reduced contractility, suggesting that the main cause of impaired contractility was abnormal energy production due to mitochondrial damage. As early as day 25, TAB2 knockout cardiomyocytes showed significant mitochondrial calcium overload, which can lead to mitochondrial damage. Furthermore, TAB2 knockout activated receptor-interacting protein kinase 1 (RIPK1), leading to an increase in mitochondrial calcium uniporter (MCU) expression, thereby augmenting the uptake of mitochondrial calcium ions. Finally, the application of the RIPK1 inhibitor Nec-1s prevents the progression of these phenotypes. Conclusions In summary, TAB2 abatement cardiomyocytes mimic dilated cardiomyopathy in vitro. This finding emphasizes the importance of using a human model to study the underlying mechanisms of this specific disease. More importantly, the discovery of a unique pathogenic pathway introduces a new notion for the future management of dilated cardiomyopathy.